Counseling on the Urgency of Establishing a Waste Bank in Creating a Green Economy in the Village - Muratno, Muratno; Fabanyo, Abdul Muid; Tahir, Usman; Tanwir, Tanwir; Widiastuti, Sri (Journal Of Human And Education (JAHE), 2024)
Waste is a problem in society that is very difficult to overcome. Waste is a scourge in society. There is still a lot of rubbish strewn about, not only on the roads, even the rivers are also polluted by rubbish. Therefore, waste is a crucial problem that requires very intensive handling from various parties. The Waste Bank provides great benefits to the community. The Waste Bank Management has support aspects that facilitate waste management, as well as problems faced in managing the Waste Bank program. The waste bank management system focuses on waste reduction and correct processing operations that are considered capable of efficiently addressing waste-related challenges. People earn money by putting waste in the Waste Bank, which provides economic benefits. People can also gain economic benefits by making craft items that can be marketed using waste recycling techniques. This Community Service is carried out in Kayo Batu Village, North Jayapura District, Jayapura City, Papua. In obtaining the data used were observation and literature review. This service activity is an effort to implement the establishment of a waste bank to realize a Green Economy in Kayo Batu Village, North Jayapura District. This effort was motivated by the lack of implementation of the establishment of a waste bank in Kayo Batu Village, North Jayapura District, which resulted in the utilization of waste in the village not being optimal. As a form of the author's thinking, several efforts and breakthroughs are offered, namely; 1.) The role of the Waste Bank for the Kayo Batu Village community in realizing a Green Economy is to improve the quality of healthier life, 2.) Increase income for people who save at the Kayo Batu Village Waste Bank to create sustainable community prosperity